Molluscs: Food Sources of Prehistoric Communities in Bukit Sarang, Bintulu, Sarawak: (Moluska: Sumber Diet Masyarakat Prasejarah Bukit Sarang, Ulu Kakus, Sarawak) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
This article focuses on the shell remains recovered during archaeological excavations carried out at Lobang Batu Puteh, Ulu Kakus, Bukit Sarang, Bintulu, Sarawak in 2003 by the Centre for Global Archaeological Research, Universiti Sains Malaysia, Penang, Sarawak Museum Department, Kuching and the Mineral and Geoscience Department Malaysia, Kuching, Sarawak. The excavations at Lobang Batu Puteh have uncovered archaeological artefacts and ecofacts radiocarbon-dated from 860 ± 50 BP to 420 ± 50 BP. Based on archaeozoological analysis, the exploited mollusc remains are from the B. episcopalis, C. nigricans, N. pulligera, R. lingulatus, Polymesoda spp. and A. striata species. Therefore, this evidence shows that the subsistence and adaptation of prehistoric societies included freshwater, brackish water, mangrove and marine environments.Keywords: prehistoric, archaezoology, shell remains, molluscs, species